Strength Training and Testosterone Treatment Have Opposing Effects on Migration Inhibitor Factor Levels in Ageing Men - D. Glintborg; L. L. Christensen; T. Kvorning; R. Larsen; K. Brixen; D. M. Hougaard; B. Richelsen; J. M. Bruun; M. Andersen (Mediators of Inflammation)
Background. The beneficial effects of testosterone treatment (TT) are debated. Methods. Double-blinded, placebo-controlled study of six months TT (gel) in 54 men aged 60–78 with bioavailable testosterone (BioT) <7.3 nmol/L and waist >94 cm randomized to TT (50–100 mg/day, n=20), placebo (n=18), or strength training (ST) (n=16) for 24 weeks. Moreover, the ST group was randomized to TT (n=7) or placebo (n=9) after 12 weeks. Outcomes. Chemokines (MIF, MCP-1, and MIP-1α) and lean body mass (LBM), total, central, extremity, visceral, and subcutaneous (SAT) fat mass established by DXA and MRI. Results. From 0 to 24 weeks, MIF and SAT decreased during ST + placebo versus placebo, whereas BioT and LBM were unchanged. TT decreased fat mass (total, central, extremity, and SAT) and increased BioT and LBM versus placebo. MIF levels increased during TT versus ST + placebo. ST + TT decreased fat mass (total, central, and extremity) and increased BioT and LBM versus placebo. From 12 to 24 weeks, MCP-1 levels increased during TT versus placebo and MCP-1 levels decreased during ST + placebo versus placebo. Conclusion. ST + placebo was associated with decreased MIF levels suggesting decreased inflammatory activity. TT may be associated with increased inflammatory activity. This trial is registered with ClinicalTrials.gov NCT00700024.